THE JOURNEY OF ISLAMIC MICROFINANCE IN INDONESIA: A SOCIAL MOVEMENT'S THEORETICAL APPROACH - Mubarrok, Ujang Syahrul; Idris, Zera Zuryana; Ulfi, Izzani (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Although Islamic Microfinance Institutions (IMFIs) have become a new and developing financial industry, the Indonesian community has not explored this organization's journey. Therefore, this study analyzes how the IMFI journey in Indonesia gained public trust and the development to date. A library research approach based on archival records and previous studies was used, and the social movement theory framework was employed to identify factors that influence society's trust in this institution. This paper shows three factors that affect the societal acceptance of IMFIs, which were, first the differences in the roles and functions of other Islamic finance organizations. Second, the passion of IMFI activists for the development and lastly, strengthening legitimacy for IMFIs is significantly needed to establish regulatory legislation. Hence, the findings in this study can become a reference for policymakers towards IMFI development in Indonesia, particularly on the uniformity of legal umbrellas applying to all types of this institution. This paper adds to the literature on IMFIs and contributes new research by employing a social movement approach in the development analysis of the organization, particularly in Indonesia.